1996
DOI: 10.1046/j.1365-2265.1996.830895.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose growth hormone replacement lowers plasma leptin and fat stores without affecting body mass index in adults with growth hormone deficiency

Abstract: Plasma leptin and total body fat fall promptly in response to low-dose replacement of GH in GH-deficient subjects. Hormone-induced changes in leptin can occur in humans in the absence of change in body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 17 publications
6
69
0
3
Order By: Relevance
“…In the whole dataset, 24-h leptin levels were the principal correlates of 24-h GH levels and they changed consensually following weight loss. Several authors 35,36 have reported that GH supplementation in GH-deficient adult patients decreased both body fat and plasma leptin concentrations. Moreover, Isokazi et al 37 showed in Zucker fa/fa rats that GH directly inhibits leptin gene expression in visceral fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the whole dataset, 24-h leptin levels were the principal correlates of 24-h GH levels and they changed consensually following weight loss. Several authors 35,36 have reported that GH supplementation in GH-deficient adult patients decreased both body fat and plasma leptin concentrations. Moreover, Isokazi et al 37 showed in Zucker fa/fa rats that GH directly inhibits leptin gene expression in visceral fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is another regulator of the GH-IGF-I axis. In rodents, leptin stimulated GH release 36 and in human elevated serum leptin in hypopituitary patients was reduced by GH treatment. 37,38 Thus an elevated leptin level and low GH level would fit the concept of a leptin resistance in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 This function is chie¯y accomplished by decreasing food consumption, 62,63 an effect probably mediated through inhibition of neuropeptide Y (NPY) secretion 64 ± 66 and enhancement of energy expenditure. 67,68 Indeed, serum leptin levels are elevated in simple obesity 69 and in clinical conditions associated with increased body fat such as Cushing's syndrome 70 and adult GH de®ciency, 71,72 and low in anorexia nervosa. 73,74 On the other side, GH also takes part in the regulation of body composition through a marked nitrogen sparing and lipolytic effect, 75 as shown by its administration to obese 76 and GH de®cient patients.…”
Section: Leptin As a Peripheral Signal For Gh Regulationmentioning
confidence: 99%